Structural dynamic analysis of tall building under wind load - Goh, Key Seng. (2009)
An equation to estimate the torsional acceleration of a tall building under wind load was derived and proposed by G.L Greig in 1980. However, the accuracy of the equation was to be determined. The Orchard Turn Tower was modelled in ETABS to obtain the mode shapes and the corresponding frequencies. Four set of wind tunnels tests results were collected from different journals published recently. A study was done to determine the effect of difference in wall and slab thickness to the natural frequency of a tall building by using ETABS. Comparison was done between results estimated from the equation derived by G.L. Greig with the results obtained from wind tunnel tests. The percentage difference was found to be significant, which varies from 400% to 2000%. A new proposed method of estimation of torsional acceleration was derived by using dynamic analysis. The results estimated by using proposed method were compared with the wind tunnel tests. The percentage difference was found to range from 283% to 1593%. The assumptions used in the derivation and several factors which may affect the results estimated were discussed. More wind tunnel tests data is needed in order to check for the reliability of the new proposed method of estimation.